Explorative analysis of gender-specific characteristics in patients with heart failure in an Italian hospital - Perrone V; Veronesi C; Nica M; Colombo D; Degli Esposti L; Castello R (Dove Medical Press, 2019)
V Perrone,1 C Veronesi,1 M Nica,2 D Colombo,2 L Degli Esposti,1 R Castello31Clicon S.R.L. Health, Economics and Outcomes Research, Ravenna, Italy; 2Novartis Pharma, Origgio, VA, Italy; 3Division of General Medicine, University Hospital of Verona, Verona, ItalyAbstract: Sex-related differences have been shown to deeply affect health-related aspects of patients. However, the lack of gender-specific analysis makes it difficult to advance personalized medicine in terms of a gender-based approach. The aim of the present study was to describe gender-specific features of patients diagnosed with heart failure (HF), with a focus on the clinical presentation. Data were collected from a properly designed database and referred to an Italian hospital. Patients aged ≥18 years with a primary or secondary diagnosis of HF between 1 January 2012 and 31 December 2016 were included, and their demographic and clinical characteristics were analyzed according to gender. Of the 719 HF patients included, 317 (44.1%) were male and 402 (55.9%) were female. Women tended to be older compared to men (82.4±8.8 years and 77.1±10.6 years, respectively). As for clinical presentation, 62.1% of female and 38.3% of male patients had preserved ejection fraction, and 56.1% of men and 58.2% of women suffered from atrial fibrillation. The left atrium was partially compromised in 62.4% of male and 63% of female patients, while right atrium dysfunction tended to be more frequent in male patients compared to female patients (29.1% and 25.5%, respectively). In conclusion, gender-specific features of a cohort of HF patients from a clinical setting were accurately described.Keywords: gender, specific characteristics, heart failure, clinical setting